مشكلات تعليم اللغة العربية لغير العرب وطرق حلها - Jailani ('ARABIYYA: JURNAL STUDI BAHASA ARAB, 2017)
Language is a mirror of civilization that is no exception for Arabic. Since the old Arabic have played a role in human civilization. In the age of globalization many challenges faced in teaching Arabic to non-Arabic. Even Arabic is a language that cannot be separated from Islam, but many Muslims who are not able to communicate in Arabic. In general the problems in developing the Arabic language to non-Arabs in addition to the lack of language environment that supports, also difficulty in getting teachers competent and professional, then it is hard to have good curriculum and tested, and the absence of interesting and creative methodology. Then the solution of all these problems, in addition to build active language, preparing teachers, curriculum, and methodology as needed, also expected the presence of international institutions that proactive in developing teaching Arabic language, as well as the Arab countries that act as donors for research in the development of teaching.